Site occupancy of interstitial deuterium atoms in face-centred cubic iron - Machida, Akihiko (Nature Pub. Group, 2014)
Hydrogen composition and occupation state provide basic information for understanding various properties of the metal–hydrogen system, ranging from microscopic properties such as hydrogen diffusion to macroscopic properties such as phase stability. Here the deuterization process of face-centred cubic Fe to form solid-solution face-centred cubic FeD(x) is investigated using in situ neutron diffraction at high temperature and pressure. In a completely deuterized specimen at 988 K and 6.3 GPa, deuterium atoms occupy octahedral and tetrahedral interstitial sites with an occupancy of 0.532(9) and 0.056(5), respectively, giving a deuterium composition x of 0.64(1). During deuterization, the metal lattice expands approximately linearly with deuterium composition at a rate of 2.21 Å(3) per deuterium atom. The minor occupation of the tetrahedral site is thermally driven by the intersite movement of deuterium atoms along the ‹111› direction in the face-centred cubic metal lattice.